Evolution of accounting systems and cryptographic means of their protection in the conditions of decentralization - Iegrashyn, Oleksandr; Pohasii, Serhii; Melnyk, Marharyta (Національний технічний університет "Харківський політехнічний інститут", 2025)
The relevance of the study. The article is devoted to an overview of the evolution of accounting systems, which are formed under the influence of the development of blockchain technologies and cryptographic protection tools. The relevance of the topic is due to the growing requirements for transparency, stability and trust in the conditions of digitalization, when centralized models increasingly demonstrate vulnerability to compromise, monopolization of control and cyber threats. The subject of research is cryptographic mechanisms: digital signatures, hash functions, commitment schemes, zero disclosure protocols, smart contracts, and selective data disclosure models that ensure authenticity, integrity, and access control in decentralized accounting systems. The purpose of the article is to conduct a theoretical and analytical review of the evolution of accounting systems: from centralized models to decentralized architectures, with a focus on the role of cryptographic mechanisms to ensure the integrity, authenticity and protection of information accounting data. Results. Key trends in the development of decentralized registries are identified, in particular the integration of SSI approaches, the optimization of consensus algorithms, the combination of on-chain and off-chain infrastructures and the increasing role of regulatory mechanisms. It is shown that modern cryptographic tools are at different stages of technological maturity and require further improvement to meet the requirements of performance, scalability and confidentiality. Conclusions. It is substantiated that cryptography is becoming a key driver of the transition to a new accounting paradigm, in which trust is provided not by centralized control, but by mathematical guarantees, transparent rules, and the possibility of open verification. Directions for further research are identified, including improving the performance of ZKP in practical applications, standardizing confidential access models, and developing adaptive architectures of decentralized systems for real business environments. Актуальність дослідження. Стаття присвячена огляду еволюції облікових систем , що формуються під впливом розвитку блокчейн-технологій та криптографічних засобів захисту. Актуальність теми зумовлена зростанням вимог до прозорості, стійкості та довіри в умовах цифровізації, коли централізовані моделі дедалі частіше демонструють вразливість до компрометації, монополізації контролю та кіберзагроз. Предметом дослідження є криптографічні механізми: цифрові підписи, хеш-функції, комітмент-схеми, протоколи нульового розголошення, смарт-контракти та моделі селективного розкриття даних, які забезпечують автентичність, цілісність і контроль доступу в децентралізованих облікових системах. Мета статті полягає у проведенні теоретико-аналітичного огляду еволюції облікових систем: від централізованих моделей до децентралізованих архітектур, із зосередженням на ролі криптографічних механізмів, для забезпеченні цілісності, достовірності та захисту інформаційних облікових даних. Результати. Визначено ключові тенденції розвитку децентралізованих реєстрів, зокрема інтеграцію SSI-підходів, оптимізацію консенсусних алгоритмів, поєднання on-chain та off-chain інфраструктур і зростання ролі регуляторних механізмів. Показано, що сучасні криптографічні інструменти перебувають на різних етапах технологічної зрілості та потребують подальшого удосконалення для відповідності вимогам продуктивності, масштабованості та конфіденційності. Висновки. Обґрунтовано, що криптографія стає ключовим драйвером переходу до нової парадигми обліку, у якій довіра забезпечується не централізованим контролем, а математичними гарантіями, прозорими правилами та можливістю відкритої верифікації. Визначено напрями подальших досліджень, серед яких підвищення продуктивності ZKP у практичних застосуваннях, стандартизація моделей конфіденційного доступу та розробка адаптивних архітектур децентралізованих систем для реальних бізнес-середовищ.
Еволюція облікових систем та криптографічні засоби їх захисту в умовах децентралізації
Keywords: decentralized accounting systems; cryptographic mechanisms; data integrity; access control; zero-knowledge proof; blockchain; децентралізовані облікові системи; криптографічні механізми; цілісність даних; контроль доступу; доказ з нульовим розголошенням; блокчейн